Prophage-mediated defence against viral attack and viral counter-defence. - Dedrick, Rebekah M; Jacobs-Sera, Deborah; Bustamante, Carlos A Guerrero; Garlena, Rebecca A; Mavrich, Travis N; Pope, Welkin H; Reyes, Juan C Cervantes; Russell, Daniel A; Adair, Tamarah; Alvey, Richard; Bonilla, J Alfred; Bricker, Jerald S; et al. (Nature Microbiology, 2017)
Temperate phages are common, and prophages are abundant residents of sequenced bacterial genomes. Mycobacteriophages are viruses that infect mycobacterial hosts including Mycobacterium tuberculosis and Mycobacterium smegmatis, encompass substantial genetic diversity and are commonly temperate. Characterization of ten Cluster N temperate mycobacteriophages revealed at least five distinct prophage-expressed viral defence systems that interfere with the infection of lytic and temperate phages that are either closely related (homotypic defence) or unrelated (heterotypic defence) to the prophage. Target specificity is unpredictable, ranging from a single target phage to one-third of those tested. The defence systems include a single-subunit restriction system, a heterotypic exclusion system and a predicted (p)ppGpp synthetase, which blocks lytic phage growth, promotes bacterial survival and enables efficient lysogeny. The predicted (p)ppGpp synthetase coded by the Phrann prophage defends against phage Tweety infection, but Tweety codes for a tetrapeptide repeat protein, gp54, which acts as a highly effective counter-defence system. Prophage-mediated viral defence offers an efficient mechanism for bacterial success in host-virus dynamics, and counter-defence promotes phage co-evolution.
175 citations (Crossref) [2023-10-31] Place: England Dedrick, Rebekah M. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania 15260, USA. Jacobs-Sera, Deborah. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania 15260, USA. Bustamante, Carlos A Guerrero. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania 15260, USA. Garlena, Rebecca A. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania 15260, USA. Mavrich, Travis N. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania 15260, USA. Pope, Welkin H. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania 15260, USA. Reyes, Juan C Cervantes. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania 15260, USA. Russell, Daniel A. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania 15260, USA. Adair, Tamarah. Department of Biology, Baylor University, Waco, Texas 76798, USA. Alvey, Richard. Biology Department, Illinois-Wesleyan University, Bloomington, Illinois 61702, USA. Bonilla, J Alfred. Biology Department, University of Wisconsin-River Falls, River Falls, Wisconsin 54016, USA. Bricker, Jerald S. Biology Department, Nebraska-Wesleyan University, Lincoln, Nebraska 68504, USA. Brown, Bryony R. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania 15260, USA. Byrnes, Deanna. Biology Department, Carthage College, Kenosha, Wisconsin 53140, USA. Cresawn, Steven G. Biology Department, James Madison University, Harrisonburg, Virginia 22807, USA. Davis, William B. School of Molecular Biosciences, Washington State University Pullman, Washington 99164, USA. Dickson, Leon A. Department of Biology, Howard University, Washington, Washington DC 20059, USA. Edgington, Nicholas P. Biology Department, Southern Connecticut State University, New Haven, Connecticut 06515, USA. Findley, Ann M. Biology, School of Sciences, University of Louisiana at Monroe, Monroe, Louisiana 71209, USA. Golebiewska, Urszula. Biological Sciences and Geology, Queensborough Community College, Bayside, New York 11364, USA. Grose, Julianne H. Biology Department, Brigham Young University, Provo, Utah 84602, USA. Hayes, Cory F. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania 15260, USA. Hughes, Lee E. Biological Sciences, University of North Texas, Denton, Texas 76203, USA. Hutchison, Keith W. Molecular and Biomedical Sciences, University of Maine, Honors College, Orono, Maine 04469, USA. Isern, Sharon. Department of Biological Sciences, Florida Gulf Coast University, Fort Myers, Florida 33965, USA. Johnson, Allison A. Biology Department, Virginia Commonwealth University, Richmond, Virginia 23284, USA. Kenna, Margaret A. Biological Sciences, Lehigh University, Bethlehem, Pennsylvania 18015, USA. Klyczek, Karen K. Biology Department, University of Wisconsin-River Falls, River Falls, Wisconsin 54016, USA. Mageeney, Catherine M. Biological Sciences, Lehigh University, Bethlehem, Pennsylvania 18015, USA. Michael, Scott F. Department of Biological Sciences, Florida Gulf Coast University, Fort Myers, Florida 33965, USA. Molloy, Sally D. Molecular and Biomedical Sciences, University of Maine, Honors College, Orono, Maine 04469, USA. Montgomery, Matthew T. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania 15260, USA. Neitzel, James. Biology Department, The Evergreen State College, Olympia, Washington 98502, USA. Page, Shallee T. Division of Environmental and Biological Sciences, University of Maine-Machias, Machias, Maine 04654, USA. Pizzorno, Marie C. Biology Department, Bucknell University, Lewisburg, Pennsylvania 17837, USA. Poxleitner, Marianne K. Biology Department, Gonzaga University, Spokane, Washington 99258, USA. Rinehart, Claire A. Biology Department, Western Kentucky University, Bowling Green, Kentucky 42101, USA. Robinson, Courtney J. Department of Biology, Howard University, Washington, Washington DC 20059, USA. Rubin, Michael R. Biology Department, University of Puerto Rico-Cayey, Cayey, Puerto Rico 00736, USA. Teyim, Joseph N. Biological Sciences, Lehigh University, Bethlehem, Pennsylvania 18015, USA. Vazquez, Edwin. Biology Department, University of Puerto Rico-Cayey, Cayey, Puerto Rico 00736, USA. Ware, Vassie C. Biological Sciences, Lehigh University, Bethlehem, Pennsylvania 18015, USA. Washington, Jacqueline. Department of Biology and Chemistry, Nyack College, Nyack, New York 10960, USA. Hatfull, Graham F. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania 15260, USA.
Keywords: *Mycobacteriophages/ph [Physiology]; *Mycobacterium smegmatis/vi [Virology]; *Mycobacterium tuberculosis/vi [Virology]; *Prophages/ph [Physiology]; DNA; Viral; DNA; Viral/ge [Genetics]; Genetic Variation; Genome; Bacterial; Genome; Viral; Ligases; Ligases/ge [Genetics]; Lysogeny; Mycobacteriophages; Mycobacteriophages/ge [Genetics]; Mycobacterium smegmatis; Mycobacterium smegmatis/ge [Genetics]; Mycobacterium tuberculosis; Mycobacterium tuberculosis/ge [Genetics]; Phylogeny; Prophages; Prophages/en [Enzymology]; Prophages/ge [Genetics]; Viral Proteins; Viral Proteins/ge [Genetics]; bacterial genome; dept.bio; enzymology; genetic variation; genetics; guanosine 3'; 5'-polyphosphate synthetases; ligase; lysogenization; mycobacteriophage; phylogeny; physiology; prophage; viral protein; virology; virus DNA; virus genome

Genome sequences of Chancellor, Mitti, and Wintermute, three subcluster K4 phages isolated using Mycobacterium smegmatis mc ^2 155 - Edgington, Nicholas P.; Voshell, Stephanie M.; Ware, Vassie C.; Akoto, Francis F.; Alhout, Alexa A.; Atwal, Gurvina J.; Balyozian, John B.; Cadieux, Zachary A.; Chop, Brianna M.; Cresawn, Steven G.; Cudkevich, Netta; Faltine-Gonzalez, Dylan Z.; et al. (Genome Announcements, 2017)
Mycobacteriophages Chancellor, Mitti, and Wintermute infect Mycobacterium smegmatis mc2155 and are closely related to phages Cheetobro and Fionnbharth in subcluster K4. Genome sizes range from 57,697 bp to 58,046 bp. Phages are predicted to be temperate and to infect the pathogen Mycobacterium tuberculosis. © 2017 Edgington et al.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/001-598-311-527-674, pop00117 tex.type: [object Object]
Keywords: Mycobacterium smegmatis; Mycobacterium tuberculosis; dept.bio; genome size; infectious agent; mycobacteriophage; nonhuman